PENINGKATKAN KEMAMPUAN KERJASAMA ANAK MELALUI PERMAINAN TRADISIONAL GOBAK SODOR - Ade Ais Ulfah Fauziah; Soni Samsu Rizal; Sarful Millah (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
In the all-digital era, gadgets are getting closer to children's lives. Children prefer to play alone with their gadgets than playing with their friends. This will reduce children's activities in group activities and it can hinder the development of children's cooperation abilities. One of the game media that can help stimulate the development of early childhood collaboration skills is the traditional gobak Sodor game, because in traditional games, the activity prioritizes children's collaboration in groups to achieve goals. The research method used was the Classroom Action Research method by Stephen Kemmis and Robin McTaggart model, while the data collection techniques used were observation and tests. The data collection instruments used were the daily learning implementation plan assessment instrument, teacher performance appraisal instrument and children's cooperation ability assessment instrument. The collected data were then analyzed using data selection techniques, data correction and data weighting. After analyzing the data, the following conclusions were obtained: 1) The ability of the teacher to compile the Daily Learning Implementation Plan through the traditional gobak Sodor game increased by 10%, in cycle I the results of the assessment reached a percentage of 80% with an average value of 79.70 while in the second cycle reaches a percentage of 90% with an average value of 90.00; 2) The teacher's ability to carry out learning with the traditional gobak Sodor game has increased by 9%, in the first cycle the assessment results reached 81% with an average value of 80.76, while in the second cycle it reached 90% with an average value of 90.15 ; 3) The ability of children's cooperation increases through the traditional gobak Sodor game as much as 15%, in the first cycle the assessment results reached 74% with an average value of 74.40, while in the second cycle it reached 89% with an average score of 89, 40. Based on the results In this research, it can be concluded that the use of the traditional gobak Sodor game can improve the ability of cooperation in group B children RA Miftahul Ulum I, Cipaku District, Ciamis Regency.